Clinical practice recommendations on lipoprotein apheresis for children with homozygous familial hypercholesterolaemia: an expert consensus statement from ERKNet and ESPN - Reijman, M. Doortje; Kusters, D. Meeike; Groothoff, Jaap W.; Arbeiter, Klaus; Dann, Eldad J.; de Boer, Lotte M.; de Ferranti, Sarah D.; Gallo, Antonio; Greber-Platzer, Susanne; Hartz, Jacob; Hudgins, Lisa C.; Ibarretxe, Daiana; et al. (Atherosclerosis, 2024)
Homozygous familial hypercholesterolaemia is a life-threatening genetic condition, which causes extremely elevated LDL-C levels and atherosclerotic cardiovascular disease very early in life. It is vital to start effective lipid-lowering treatment from diagnosis onwards. Even with dietary and current multimodal pharmaceutical lipid-lowering therapies, LDL-C treatment goals cannot be achieved in many children. Lipoprotein apheresis is an extracorporeal lipid-lowering treatment, which is used for decades, lowering serum LDL-C levels by more than 70% directly after the treatment. Data on the use of lipoprotein apheresis in children with homozygous familial hypercholesterolaemia mainly consists of case-reports and case-series, precluding strong evidence-based guidelines. We present a consensus statement on lipoprotein apheresis in children based on the current available evidence and opinions from experts in lipoprotein apheresis from over the world. It comprises practical statements regarding the indication, methods, treatment goals and follow-up of lipoprotein apheresis in children with homozygous familial hypercholesterolaemia and on the role of lipoprotein(a) and liver transplantation.
Online verfügbar 27 March 2024, Version des Artikels 9 April 2024
Gesehen am 29.11.2024